Pengaruh Kombinasi Masase Punggung dan Masase Effleurage Menggunakan Aromaterapi Melati Terhadap Intensitas Nyeri Disminorea Pada Santriwati di Pondok Pesantren Qamarul Huda Bagu - Asmawariza, Lalu Hersika; Nurwahida, Nurwahida (Progres Ilmiah Kesehatan, 2021)
Background: Dysmenorrhea is abdominal pain that comes from uterine cramps and occurs during menstruation. Treatment uses non-pharmacological methods, one of which is using the massage method to reduce pain during menstruation, one of which is a combination of back massage and effleurage massage using jasmine therapy aroma. The purpose of this study was to determine the effect of a combination of back massage and effleurage massage using jasmine aromatherapy on the intensity of dysmenorrhea pain among female students at Qamarul Huda Bagu Islamic boarding school. Research Methods: The research design in this study used a quasy experimental with a pretest and posttest control group. The sample of this study was 52 female students with dysmenorrhea with simple random sampling technique. The test used was the paired t test with an error rate of ? = 0.05. Results: The results of the paired sample t test obtained a combination of back massage and effleurage massage on the intensity of dysmenorrheal pain p value = 0.001. This shows that p value = 0.001 <? = 0.05 then H0 is rejected and H1 is accepted. Conclusion: There is an effect of combination back massage and massage using aromatherapy on the intensity of dysmenorrhea pain.